Analisis Dampak Keluarga Broken Home Pada Perilaku Siswa - Binti Nuraisyah; Zaenal Abidin; Anisa Fadilah Hidayati; Aryeni Ika Febriyana (STIKes Ibnu Sina Ajibarang, 2024)
This research article aims to identify the influence of a broken home among parents on student behavior and to identify solutions that can be applied to children as a result of a broken home. Research results show that children from broken homes tend to experience higher levels of stress, anxiety and depression. Changes in their daily lives, conflict between parents, and insecurity can contribute to these psychological problems. In addition, conductive behavior such as bad company and involvement in detrimental behavior can also have a significant negative impact. The research uses library methods or known as (library research). The data collection technique in this research was to examine various kinds of literature in the form of books, journals, e-books and literature relevant to the impact of broken home families on student behavior